Virtual Tours: Video, Photo, and VR. - Torres, Francis; Harrington, Richard (linkedin.com, 2019)
Showcase a space or experience by creating a virtual tour. Learn how to create floor plans, shoot 360° video and photos, and piece together all of your 360° assets to build a tour.